Design considerations for optogenetic applications of soft micro-LED-based device systems across diverse nervous systems - Ju Young Lee; Taemin Kim; Shinil Cho; Jiho Shin; Woon-Hong Yeo; Tae Soo Kim; Ki Jun Yu (Bioactive Materials)
Optogenetics enables precise, cell-specific control of neural activity, surpassing traditional electrical stimulation methods that indiscriminately activate nearby cells, making it crucial for rehabilitation, neurological disorder treatment, and understanding neural circuits. Among light sources for delivering light to genetically modified cells, bio-implants integrated with Light Emitting Diodes (LEDs) have recently been the focus of extensive research due to their advantage of enabling local photogeneration. Unlike laser-based systems, which require tethered setups that hinder behavioral experiments, μ-LED-based devices allow for wireless operation, facilitating more natural movement in subjects. Furthermore, μ-LED arrays can be designed with higher spatial resolution compared to waveguide-coupled external light sources, enabling more precise control over neural activity. This paper presents design rules for implantable flexible optogenetic devices based on μ-LED, tailored to the unique anatomical and functional requirements of various regions of the nervous system. Integration of recent advancements in devices with μ-LEDs (e.g. wireless systems, optofluidic systems, multifunctionality, and closed-loop systems) enhances behavioral experiments and deepens understanding of complex neural functions in the brain, spinal cord, autonomic nervous system, and somatic nervous system. The combination of optogenetics with advanced bio-implantable devices offers promising avenues in medical science, providing more effective tools for neuromodulation research and clinical applications.